Between Democracy and The Role of The Military: A Study of The Polemic of Indonesian National Armed Forces Regulation’s Revision in Indonesia - Purbasari, Verbena Ayuningsih; R. Samidi; Galih Kurniawan, Bekti; Rosalina Marsudi, Kenlies Era (Jurnal Ilmu Pemerintahan : Kajian Ilmu Pemerintahan dan Politik Daerah, 2026)
This study aims to analyze the perspectives of Generation Z at the undergraduate level regarding the process of drafting the Indonesian military law from a democratic point of view. Using a qualitative field research approach, primary data was collected through in-depth interviews. Secondary data was obtained from official documents and academic literature. The data was analyzed using Miles and Huberman's interactive model, supported by source triangulation for validation. The findings show that students view the legislative process as lacking transparency, public participation, and accountability, contrary to the principles of substantive democracy. Controversial provisions were found to open up opportunities for militaristic practices and weaken democratic control. This study highlights the critical awareness of Generation Z, which functions as a social watchdog, reflecting their role as moral guardians and agents of democracy. Through discussions, demonstrations, judicial reviews, and policy dialogues, students fight for transparent governance and the strengthening of civilian supremacy. This research emphasizes the urgency of inclusive participation in the legislative process to maintain the integrity of democracy in Indonesia.